UI/UX Design of Kiddy Rent Marketplace Application Using the User-Centered Design Method - Risty Farentina; Seftin Fitri Ana Wati; Nambi Sembilu (bit-Tech, 2025)
Marketplace is one of the fastest growing digital innovations in the current technological era, which offers increased effectiveness and efficiency in product and service transactions. In the children's equipment and toy rental sector, it has the potential to help connect service providers and renters practically. However, the current rental process still faces several challenges, including manual procedures, lack of complete information, and low transaction efficiency, all of which hinder the rental experience and reduce user satisfaction. Therefore, it is important to design the UI/UX of a marketplace application that meets user needs and achieves a high level of usability. This study aims to design the UI/UX of the Kiddy Rent application, a marketplace specifically created for renting children's equipment and toys, using the User-Centered Design (UCD) approach to ensure that the final solution is tailored to user needs. The UCD stages applied include Understanding the Context of Use, Specifying User Requirements, Producing Design Solutions, and Evaluating Against Requirements. The resulting prototype was evaluated using two methods, namely Heuristic Evaluation and Usability Testing based on the ISO 9241-11 standard, by applying the System Usability Scale (SUS) to measure satisfaction. The evaluation results show that the application obtained a SUS score of 85.5, which is categorized as "Excellent", and entered the B grade with an acceptance level of "Acceptable". These findings indicate that the developed design not only meets user expectations but also has strong potential to provide an effective, efficient, and satisfying experience in the digital rental process.